Thrombogenicity of the p48 and anti-thrombogenic p48 hydrophilic polymer coating low-profile flow diverters in an in vitro human thrombin generation model. Issue 4 (August 2020) - Bhogal, Pervinder; Lenz-Habijan, Tim; Bannewitz, Catrin; Hannes, Ralf; Monstadt, Hermann; Brodde, Martin; Kehrel, Beate; Henkes, Hans
Objectives: The implantation of flow diverters, or stents in general, necessitates the use of dual anti-platelet treatment with typical regimes including aspirin and a P2Y12 inhibitor. This carries an inherent risk of haemorrhage. We sought to compare the thrombogenicity of the anti-thrombogenic p48 hydrophilic polymer coating compared to the standard uncoated p48 flow diverter using an in vitro thrombogenicity assay. Methods: To evaluate the thrombin generation influenced by the different stent types the stents were placed in wells of a 24-well plate with the addition of plasma from healthy volunteers the thrombin calibrator respectively the PPP-reagent was added. Subsequently, the thrombin substrate was added and the thrombin generation was analysed every 60 s using a thrombinoscope. The assay is calibrated using samples containing a known amount of active thrombin in PPP. Thrombin activity is proportional to the change in fluorescence. Results: The p48 hydrophilic polymer coating shows a significantly lower peak thrombin concentration (1.13 ± 0.21 vs. 1.41 ± 0.22) and longer time to peak thrombin concentration (0.96 ± 0.04 vs. 0.74 ± 0.07) compared to the uncoated p48 device ( p < 0.01). The responses of the p48 hydrophilic polymer coating were similar to that of the negative control. Conclusion: The hydrophilic polymer coating surface modification significantly reduces the thrombogenicity of the p48 flow diverter. These results corroborate the findings from previous in vitro studies.